Read! write! publish! : making books in the classroom grade 1-5 - Fairfax, Barbara (Cypress, CA : Creative Teaching Press, Inc, 1992)
Step-by-step directions for 20 books. 120 integrated writing ideas. Literature titles that motivates writing
Keywords: Classroom activities; Writing